Influence Of Audit Tenure, Company Size, And Audit Committee Against Audit Report Lag With Specialization Moderation Variables Auditor Industry (Prosiding Simposium Ilmiah Akuntansi, 2024)
The purpose of this study was to determine the effect of audit tenure, firm size, audite committee, on audit report lag with auditor industryspecialization as moderating. Researchers use quantitative research. The population in this study were all companies in food and beverages sector listed on the Indonesia Stock Exchange totaling 26 companies which were always listed for 5 consecutive years. The sample was selected using purposive sampling and obtained 60 research objects. The results of the study audit tenure, firm size, and audite committee have an effect on audit report lag. Auditor industry specialization as moderating is able to strengthen the effect influence of the audit tenure, firm size, and audite committee on the auditor industry specialization.